Pengaruh Sistem Pengendalian Manajemen Dan Budaya Organisasi Terhadap Kinerja Manajerial Pada Bank Syariah Indonesia, Kc Aceh Diponegoro - Rudy Fachruddin; Ikhsan Ikhsan (Jurnal Riset AKuntansi dan Bisnis, 2026)
This study aims to determine simultaneously and partially the influence of management control system and organizational culture on managerial performance at Bank Syariah Indonesia, Banda Aceh. This study used quantitative research methods using questionnaires as the main primary data source. The population in this study is all managers and employees of Bank Syariah Indonesia Aceh Area  with purposive sampling technique  with a total of 35 respondents. The analysis method used in this study is multiple linear regression analysis with SPSS 26 tools. The results showed that management control system variables partially had no effect on managerial performance, while organizational culture variables had an effect on managerial performance at Bank Syariah Indonesia, Banda Aceh. Then simultaneously the variables of management control system and organizational culture affect managerial performance at Bank Syariah Indonesia Banda Aceh.